Improvement of the perovskite photodiodes performance via advanced interface engineering with polymer dielectric - Andrey P. Morozov; Lev O. Luchnikov; Sergey Yu. Yurchuk; Artur R. Ishteev; Pavel A. Gostishchev; Sergey I. Didenko; Nikita S. Saratovsky; Dmitry O. Balakirev; Ivan V. Dyadishchev; Andrey A. Romanov; Ekaterina A. Ilicheva; Anton A. Vasilev; et al. (Light: Advanced Manufacturing)
Halide perovskite-based photodiodes are promising for efficient detection across a broad spectral range. Perovskite absorber thin-films have a microcrystalline morphology, characterized by a high density of surface states and defects at inter-grain interfaces. In this work, we used dielectric/ferroelectric poly(vinylidene-fluoride-trifluoroethylene) (P(VDF-TrFE)) to modify the bulk interfaces and electron transport junction in p-i-n perovskite photodiodes. Our complex work demonstrates that interface engineering with P(VDF-TrFE) induces significant Fermi level pinning, reducing from 4.85 eV for intrinsic perovskite to 4.28 eV for the configuration with dielectric interlayers. Modifying the interfaces in the devices resulted in an increase in the key characteristics of photodiodes compared to pristine devices. The integration of P(VDF-TrFE) into the perovskite film didn’t affect the morphology and crystal structure, but significantly changed the charge transport and device performance. IV curve analysis and 2-diode model calculations showed enhanced shunt properties, a decreased non-ideality factor, and reduced saturation dark current. We have shown that the complex introduction of P(VDF-TrFE) into the absorber’s bulk and on its surface is essential to reduce the impact of the trapping processes. For P(VDF-TrFE) containing devices, we increased the specific detectivity from 1011 to ~1012 Jones, expanded the linear dynamic range up to 100 dB, and reduced the equivalent noise power to 10−13 W·Hz−1/2. Reducing non-radiative recombination contributions significantly enhanced device performance, improving rise/fall times from 6.3/10.9 µs to 4.6/6.5 µs, and achieved photo-response dynamics competitive with state-of-the-art analogs. The cut-off frequency (3dB) increased from 64.8 kHz to 74.8 kHz following the introduction of the dielectric. We also demonstrated long-term stabilization of PPD performance under heat-stress. These results provide new insights into the use of organic dielectrics and an improved understanding of trap-states/ion defect compensation for detectors based on perovskite heterostructures.